Insomnia and sleepiness during pregnancy: Associations with gestational diabetes mellitus - Forsbom, Otto; Perasto, Laura; Aukia, Linda; Paavonen, E. Juulia; Mattila, Inka; Reinilä, Sanni; Karlsson, Hasse; Karlsson, Linnea; Polo-Kantola, Päivi (Wiley, 2026)
Introduction: Sleep quality typically deteriorates during pregnancy, and poor sleep is a risk factor for pregnancy complications, including gestational diabetes mellitus (GDM). The present study is the first longitudinal study addressing associations between sleep quality and GDM at separate time-points throughout the pregnancy.
Material and methods: This study was a part of the FinnBrain cohort, including 3808 pregnant women. Sleep quality was assessed using the Basic Nordic Sleep Questionnaire four times during pregnancy, and GDM was diagnosed by glucose tolerance testing. Four groups were formed: non-GDM, GDM, and two subgroups of GDM (medical nutritional therapy and GDM with pharmacotherapy). Paired comparisons within the groups between different time-points were conducted, and cross-sectional logistic regression analyses were carried out. The results were adjusted by maternal age, body mass index, parity, education, smoking, mood symptoms, and pre-eclampsia.
Results: In paired comparisons between time-points, the insomnia score increased during pregnancy, albeit similarly in the GDM and non-GDM groups. However, the pattern of changes in sleepiness score differed between the groups during pregnancy. In the non-GDM group, mean scores showed a U-shape, decreasing in mid-pregnancy. This decrease was not observed in the GDM group, with scores remaining similar between early and mid-pregnancy and higher compared with the non-GDM group. These differences were more pronounced in the pharmacotherapy subgroup. In the cross-sectional analysis, only a few differences emerged between the groups. Women in the GDM group were more likely to report poor general sleep quality in mid-pregnancy compared with women in the non-GDM group (aOR 1.4, 95% CI 1.0-1.9, p = 0.037), but no differences in distinct insomnia symptoms emerged. Sleepiness symptoms were more common in the GDM group in early pregnancy (aOR 1.1, 95% CI 1.0-1.1, p = 0.028) and in mid-pregnancy (aOR 1.1, 95% CI 1.0-1.1, p = 0.030). Women in the GDM pharmacotherapy subgroup reported daytime napping more often in mid-pregnancy (aOR 1.8, 95% CI 1.0-3.3, p = 0.049).
Conclusions: Insomnia was found to increase as pregnancy proceeds, independently of GDM. However, the decrease in sleepiness found in women without GDM in mid-pregnancy was not observed in women with GDM, possibly indicating that the effectiveness of sleep is compromised in GDM patients.